PENDIDIKAN SUSILA PADA PENGGUNAAN ANGGAH-UNGGUHING BASA BALI DALAM PERGAULAN MODERN - Agung Jaya Suryawan (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
Respect in speaking Balinese will create an antipathy attitude towards Balinese. Therefore, the Balinese language (especially a form of respect) must be managed properly so as not to create an antipathic attitude towards Balinese, especially by future generations. It is important to make an agreement and understanding of the Balinese people themselves in order to maintain the great Balinese culture! All of this can work well if formal educational institutions want to improve, want to review Balinese language teaching materials from kindergarten to tertiary levels. In making teaching materials, it is appropriate to adopt elements of regional culture and modern culture in a balanced manner. Thus, in terms of maintenance (local elements) and development (modern elements) there will be a balance so that the Balinese language is able to survive and is in demand by its speakers. Furthermore, in making teaching materials, the government (in this case the Education Office) involves experts in the field of Balinese language learning.Keywords: Ethical Education, Anggah-Ungguhing Basa Bali